Westbound [large type] - Richards, Dusty; Mayo, Matthew P. (Battling Harrigans of the frontier, 2023)
"Mackworth "Mack" Harrigan's family legacy burned to the ground in the spring of 1849. The Ohio mill that brought them prosperity was now cinder and ash, and his ruthless father perished in the flames along with their fortune. If the Harrigans have a future, it lies out west in open country where they can build whatever lives they choose. Mack knows his wife Ell, and their children Kane, Meghan, and Fitch are more than capable of overcoming the challenges of their journey. For the untamed frontier is full of seriously deadly battles. From a rough river voyage to wagon train travel across desert lands plagued by dust storms, the Harrigans encounter desperados and merciless killers who view them as little more than prey. And as Mack and his family adapt to their merciless surroundings, they realize they must enforce their own laws and dispense their own justice . . ."--